Amphiphilic peptide coated superparamagnetic iron oxide nanoparticles for in vivo MR tumor imaging. Issue 51 (9th May 2016) - Ozdemir, Ayse; Ekiz, Melis Sardan; Dilli, Alper; Guler, Mustafa O.; Tekinay, Ayse B.
Abstract : The co-assembled SPION/PA system with its biocompatible and biodegradable properties can be considered as effective nanocomposite system for MR imaging. Abstract : Magnetic resonance imaging (MRI) is a noninvasive imaging technique that provides high spatial resolution and depth with pronounced soft-tissue contrast for in vivo imaging. A broad variety of strategies have been employed to enhance the diagnostic value of MRI and detect tissue abnormalities at an earlier stage. Superparamagnetic iron oxide nanoparticles (SPIONs) are considered to be suitable candidates for effective imaging due to their small size, versatile functionality and better biocompatibility. Here, we demonstrate that coating SPIONs with proline-rich amphiphilic peptide molecules through noncovalent interactions leads to a water-dispersed hybrid system suitable as an MRI contrast agent. Cellular viability and uptake of amphiphilic peptide coated SPIONs (SPION/K-PA) were evaluated with human vascular endothelial cells (HUVEC) and estrogen receptor (ER) positive human breast adenocarcinoma (MCF-7) cells. The efficiency of SPION/K-PA as MRI contrast agents was analyzed in Sprague-Dawley rats with mammary gland tumors. MR imaging showed that SPION/K-PA effectively accumulated in tumor tissues, enhancing their imaging potential. Although nanoparticles were observed in reticuloendothelial system organs (RES) and especially in the liver and kidney immediately after administration, the MR signal intensity in these organs diminished after 1 h and nanoparticles were subsequently cleared from these organs within two weeks. Histological observations also validated the accumulation of nanoparticles in tumor tissue at 4 h and their bioelimination from the organs of both healthy and tumor-bearing rats after two weeks.